2022
DOI: 10.5089/9798400208126.001
|View full text |Cite
|
Sign up to set email alerts
|

For Whom the Bell Tolls: Climate Change and Inequality

Abstract: For Whom the Bell Tolls: Climate Change and Inequality Prepared by Serhan Cevik and João Tovar Jalles 1 Authorized for distribution by Alfredo Cuevas May 2022 IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In particular, the impact of climate change vulnerability on income distribution is more pronounced in developing countries, largely due to their weaker capacity for climate change adaptation and mitigation. The study also points out that income inequality should be explicitly considered when designing climate change adaptation and mitigation policies to protect the most vulnerable and address disparities equitably [2].…”
Section: For Whom the Bell Tolls: Climate Change And Income Inequalitymentioning
confidence: 99%
“…In particular, the impact of climate change vulnerability on income distribution is more pronounced in developing countries, largely due to their weaker capacity for climate change adaptation and mitigation. The study also points out that income inequality should be explicitly considered when designing climate change adaptation and mitigation policies to protect the most vulnerable and address disparities equitably [2].…”
Section: For Whom the Bell Tolls: Climate Change And Income Inequalitymentioning
confidence: 99%
“…In a more recent study by Cevik and Jalles (2022) on the linkage between climate change and income inequality, a panel of 158 countries was explored spanning the period 1955-2019. The researchers found that the increase in climate change vulnerability leads to an increase in income inequality.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There have been several major epidemics (both established and emerging) since 2000 (Figure 3). 7 In the last 15 years alone six public health emergencies of international concern have been declared by the WHO (Wilder-Smith and Osman 2020). Nonetheless, despite major advances in medical sciences global preparedness has not been adequate.…”
Section: Strengthening Pandemic Preparednessmentioning
confidence: 99%